Nonsurgical rhinoplasty: prevention and management of associated complications. Issue 4 (August 2022) - Mella, Jeffrey; Oyer, Samuel
Abstract : Purpose of review: Nonsurgical rhinoplasty (NSR) continues to grow in demand and popularity. Consequently, there has been a rise in the number of reported complications. This review will summarize and discuss the current evidence for the prevention and management of adverse events related to NSR with a specific emphasis on practical clinical applications. The review is based on recent systematic reviews and multidisciplinary expert consensus recommendations. Recent findings: First, NSR has overall favorable outcomes with rare complications. Second, vascular compromise is a rare event, but the number of reported severe complications is rising. Third, providers should be intimately familiar with preventive measures, early signs and symptoms, and appropriate management algorithms of all possible complications. Fourth, having a readily available 'toolbox' of recommended therapies may improve timely management of emergent complications. Summary: The number of complications associated with NSR is expected to rise congruent with the increased demand for the procedure. Although NSR has a favorable safety profile, complications can occur in the best of hands even when using appropriate risk reduction strategies. Early detection and appropriate treatment of known complications may eliminate or minimize sequelae and allow providers to continue to safely perform NSR.